K2-280 b – a low density warm sub-Saturn around a mildly evolved star. Issue 4 (17th July 2020) - Nowak, Grzegorz; Palle, Enric; Gandolfi, Davide; Deeg, Hans J; Hirano, Teruyuki; Barragán, Oscar; Kuzuhara, Masayuki; Dai, Fei; Luque, Rafael; Persson, Carina M; Fridlund, Malcolm; Johnson, Marshall C; et al.
ABSTRACT: We present an independent discovery and detailed characterization of K2-280 b, a transiting low density warm sub-Saturn in a 19.9-d moderately eccentric orbit ( e = 0.35_-0.04^+0.05 ) from K2 campaign 7. A joint analysis of high precision HARPS, HARPS-N, and FIES radial velocity measurements and K2 photometric data indicates that K2-280 b has a radius of R b = 7.50 ± 0.44 R⊕ and a mass of M b = 37.1 ± 5.6 M⊕, yielding a mean density of ρb = 0.48 _ - 0.10 ^ + 0.13 g cm^-3 . The host star is a mildly evolved G7 star with an effective temperature of T eff = 5500 ± 100 K, a surface gravity of g_ = 4.21 ± 0.05 (cgs), and an iron abundance of [Fe/H] = 0.33 ± 0.08 dex, and with an inferred mass of M ⋆ = 1.03 ± 0.03 M⊙ and a radius of R ⋆ = 1.28 ± 0.07 R⊙ . We discuss the importance of K2-280 b for testing formation scenarios of sub-Saturn planets and the current sample of this intriguing group of planets that are absent in the Solar system.